The Gut Microbiota and Irritable Bowel Syndrome: Friend or Foe? - Ghoshal, Uday C. (Hindawi Publishing Corporation, 2012)
Progress in the understanding of the pathophysiology of irritable bowel syndrome (IBS), once thought to be a purely psychosomatic disease, has advanced considerably and low-grade inflammation and changes in the gut microbiota now feature as potentially important. The human gut harbours a huge microbial ecosystem, which is equipped to perform a variety of functions such as digestion of food, metabolism of drugs, detoxification of toxic compounds, production of essential vitamins, prevention of attachment of pathogenic bacteria to the gut wall, and maintenance of homeostasis in the gastrointestinal tract. A subset of patients with IBS may have a quantitative increase in bacteria in the small bowel (small intestinal bacterial overgrowth). Qualitative changes in gut microbiota have also been associated with IBS. Targeting the gut microbiota using probiotics and antibiotics has emerged as a potentially effective approach to the treatment of this, hitherto enigmatic, functional bowel disorder. The gut microbiota in health, quantitative and qualitative microbiota changes, and therapeutic manipulations targeting the microbiota in patients with IBS are reviewed in this paper.